Análise numérica do desempenho e das emissões de poluentes em um motor monocilíndrico de pesquisa aplicando-se o sistema de pré-câmara passiva e operando com etanol hidratado - Mateus Silva Mendonça (2023)
The internal combustion engines have been changing over time, aiming that they have better efficiencies combined to lower pollutant emissions. One of the ways to achieve these improvements is through the application of a pre-chamber ignition system, whose its parameters must be adjusted aiming its better optimization. Besides, the use of numerical simulation is essential to reduce time of costly experimental tests and consequently to optimize the development of an internal combustion engine. In this way, unidimensinal and tridimensional numerical simulations of a single-cylinder research engine were performed with the support of the softwares GT-SUITE and CONVERGE, respectively, and they included different operation conditions of this engine that operated with stoichiometric air-fuel mixture and hydrated ethanol, biofuel available on a large scale in Brazil through production using sugarcane, which allows the absorption of CO2 from the atmosphere stand out. The numerical simulations encompassed two configurations of the engine: the first related to the conventional ignition model using spark and the second related to the model whose ignition is provided with the auxiliary of a passive pre-chamber ignition system aiming the turbulent jet ignitions, allowing in this way to compare the improvements obtained by the second configuration to the first one. Throughout this numerical methodology were still performed steps to simulate a flux bench with the support of CONVERGE as well those ones related to mesh, reaction mechanism and cycle tests. The results demonstrated that, compared to the conventional ignition system, the pre-chamber ignition system studied was able to deliver both a combustion rate up to 27.4% faster, thus favoring the increase in the compression ratio for obtaining of greater thermal and fuel conversion efficiencies, as well as a reduction of up to 27.0% and 29.5% of carbon monoxide and nitrogen oxides emissions, respectively, with the optimization of the geometry of the pre-chamber being essential to achieve these improvements. Still in this comparison, it was possible to observe that the configurations with pre-chamber reached thermal, combustion and fuel conversion efficiencies up to 1.5%, 6.0% and 3.7% higher, respectively.